Internal migration and crime in Brazil - Eva-Maria Egger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Empirical evidence suggests that the social effects of internal migration may be substantially different from those associated with the arrival of international migrants. In this paper, I provide the first evidence of the effect of internal migration on crime with longitudinal data from Brazilian microregi\~oes. Using local labour demand shocks in the manufacturing sector as an instrument for migratory flows, I find that a 10 per cent increase in the in-migration rate translates into a 6 per cent increase in the homicide rate in destinations. Exploring possible channels, I do not find that crime-prone migrants drive the results. The effect is only significant in locations with high past crime rates, indicating crime inertia, and in places with a small informal sector, suggesting that the impact of internal migration is conditioned by the ability of local labour markets to accommodate migrants.
Keywords: J61; K42; R23; 330; Brazil; crime; internal migration